Determination of Fatty Acid Methyl Ester Composition of Mango (Mangifera indica L.) Kernel Oil and Tribological Properties of its Triesters - Y. Jethro; A. O. Oyewale; I. Abdulkadir (Journal of Applied Sciences and Environmental Management, 2023)
Conventional process of Soxhlet extraction with n-Hexane was used to extract Mango kernel (Mangifera indica L.) oil for determination of fatty acid methyl ester composition of mango (Mangifera indica L.) kernel oil and tribological properties of its triesters and a percentage extractable of 8.4 % was obtained. A twostep process of esterification and transesterification was employed to produce fatty acid methyl ester (FAME) from M. indica kernel oil refers to as Mango kernel methyl ester (MKME). Double esterification of the MKME with trimethylolpropane (TMP) in the presence of sodium methoxide yielded 95 % Mango oil based trimethylolpropane ester (MOTE). Anotherof the MKME was used to synthesize Biolubricant using the conventional epoxidation process to produce 70 % Mango oil based epoxidised biolubricant (MEB-L). Tribological test was conducted on the MOTE and MEB-L at coefficient of friction ranging from 0.03 to 0.18 µ on Aluminum alloy with load of 8.00 N. The mean value of coefficient of friction were determined to be 0.083 µ and 0.080 µ for MOTE and MEB-L respectively. Although MEB-L present a slightly better frictional performance than MOTE, both values are within an acceptable mean with regards to the suitability of MOTE and MEB-L as potential substitute to conventional lubricant